Swimming performance of Bradyrhizobium diazoefficiens is an emergent property of its two flagellar systems - Quelas, Juan Ignacio (2016)
Many bacterial species use flagella for self-propulsion in aqueous media. In the soil, which is a complex and structured environment, water is found in microscopic channels where viscosity and water potential depend on the composition of the soil solution and the degree of soil water saturation. Therefore, the motility of soil bacteria might have special requirements. An important soil bacterial genus is Bradyrhizobium, with species that possess one flagellar system and others with two different flagellar systems. Among the latter is B. diazoefficiens, which may express its subpolar and lateral flagella simultaneously in liquid medium, although its swimming behaviour was not described yet. These two flagellar systems were observed here as functionally integrated in a swimming performance that emerged as an epistatic interaction between those appendages. In addition, each flagellum seemed engaged in a particular task that might be required for swimming oriented toward chemoattractants near the soil inner surfaces at viscosities that may occur after the loss of soil gravitational water. Because the possession of two flagellar systems is not general in Bradyrhizobium or in related genera that coexist in the same environment, there may be an adaptive tradeoff between energetic costs and ecological benefits among these different species.